RNA-Seq Time Series of Vitis vinifera Bud Development Reveals Correlation of Expression Patterns with the Local Temperature Profile - Boas Pucker; Anna Schwandner; Sarah Becker; Ludger Hausmann; Prisca Viehöver; Reinhard Töpfer; Bernd Weisshaar; Daniela Holtgräwe (Plants, 2020)
Plants display sophisticated mechanisms to tolerate challenging environmental conditions and need to manage their ontogenesis in parallel. Here, we set out to generate an RNA-Seq time series dataset throughout grapevine (Vitis vinifera) early bud development. The expression of the developmental regulator VviAP1 served as an indicator of the progression of development. We investigated the impact of changing temperatures on gene expression levels during the time series and detected a correlation between increased temperatures and a high expression level of genes encoding heat-shock proteins. The dataset also allowed the exemplary investigation of expression patterns of genes from three transcription factor (TF) gene families, namely MADS-box, WRKY, and R2R3-MYB genes. Inspection of the expression profiles from all three TF gene families indicated that a switch in the developmental program takes place in July which coincides with increased expression of the bud dormancy marker gene VviDRM1.